EVALUATION OF MODEL FOR END-STAGE LIVER DISEASE SCORE CUT OFF VALUES IN PATIENTS WITH HEPATIC ENCEPHALOPATHY - Khurram, Muhammad; Qayyum, Wajeeha; Umar, Muhammad; Abedin, Zain ul; Bushra, Hamama Tul (Journal of Ayub Medical College Abbottabad, 2015)
Background: Model for End Stage Liver Disease (MELD) is scoring system used for prioritization of patients waiting liver transplantation. Patients with decompensated chronic liver disease (DCLD) with higher MELD score and hepatic encephalopathy (HE) have poor outcome. We planned to note association between short term mortality and various cut-off values of at admission MELD score in HCV related DCLD patients presenting with HE. Methods: In this descriptive case series, 208 Hepatitis C (HCV) related chronic liver disease (CLD) patients with HE were included. At admission serum bilirubin, creatinine and INR were sought to calculate MELD score. Patients who improved were discharged and kept under regular follow up. Outcome was categorized into alive or expired in 3 months after admission. Based on MELD score cut off values of >15, >20, >25 and >30, association with outcome was determined using Chi-square test. Results: One hundred and six (51%) patients were female. Mean patient age was 55.3±10.6 years. Outcome wise, 128 (61.5%) were alive and 80 (38.5%) expired. Mean MELD score of expired was 22.17±9.14. 55 (51%) patients with MELD score >15, 44 (65.7%) patients with >20, 30 (73.2%) patients with >25, and 21 (72.5%) patients with >30 expired. MELD score >20 had strongest association with outcome, p value less than o.01. Conclusion: At admission MELD score >20 are most significantly associated with poor outcome in DCLD patients with HE.